2021
DOI: 10.1021/acs.jpcc.0c10171
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transfer from Photoexcited Semiconducting Single-Walled Carbon Nanotubes to Wide-Bandgap Wrapping Polymer

Abstract: As narrow optical bandgap materials, semiconducting single-walled carbon nanotubes (SWCNTs) are rarely regarded as charge donors in photoinduced charge-transfer (PCT) reactions. However, the unique band structure and unusual exciton dynamics of SWCNTs add more possibilities to the classical PCT mechanism. In this work, we demonstrate PCT from photoexcited semiconducting (6,5) SWCNTs to a wide-bandgap wrapping poly-[(9,9-dioctylfluorenyl-2,7-diyl)- alt -(6,6′)-(2,2′-bipyridine)] (PFO–BPy)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…For polymer-wrapped (6,5) SWCNTs in tetrahydrofuran, it was observed that the overall decay times were slightly elongated for excitation to higher excitonic levels such as the E 22 or E 33 . 47 The k 5 values should be essentially similar; however, the increased noise level at later times makes the fit less reliable, and the stated fit error likely underestimates the real uncertainty.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For polymer-wrapped (6,5) SWCNTs in tetrahydrofuran, it was observed that the overall decay times were slightly elongated for excitation to higher excitonic levels such as the E 22 or E 33 . 47 The k 5 values should be essentially similar; however, the increased noise level at later times makes the fit less reliable, and the stated fit error likely underestimates the real uncertainty.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In case of UP excitation, the first two decays are about twice as fast as for E22 excitation. We attribute the slower decays for E22 excitation to the delay caused by the required internal relaxation to the E11 state (~ 100 fs) 47 and subsequent population of the UP by the dark polariton states. This evolution of the proposed UP to biexciton transition approximately follows the evolution of the LP feature (at 1.1 eV in Figure 3a and 3b).…”
Section: Decay Associated Difference Spectra (Dads)mentioning
confidence: 98%
See 1 more Smart Citation
“…Each corona phase can influence the fluorescence emission of the SWCNTs, due to its density and/or interactions with the SWCNT surface. Fluorescence emission of a certain chirality can be altered by the distinct dielectric environment that the corona phase induces around the SWCNTs or even charge transfer effects from the wrapping molecules to the SWCNT or vice versa. , Our PEG-dendrons are bound to the SWCNTs via end groups that differ in the type of their interaction with the graphene lattice. While π–π stacking of the SWCNT with the aromatic end groups is possible, hydrophobic interactions are expected in the case of the aliphatic end groups.…”
Section: Resultsmentioning
confidence: 99%
“…A carbon nanotube is a typical one-dimensional carbon material with excellent physical properties and has attracted tremendous attention in the past three decades since its discovery. Carbon nanotube-based dry adhesive is one of the main routes for the fabrication of gecko-inspired artificial adhesives and has aroused research interests due to the material capability of achieving the real gecko structure. The outstanding adhesion properties of carbon nanotubes (CNTs) are believed to originate from van der Waals (vdW) interactions at the micro- and nanoscale interface when contacting other surfaces . The vdW interaction mainly includes dipole–dipole, dipole–induced dipole, and dispersion interactions, which are essentially the electrostatic interactions between different charge centers. , Meanwhile, contact electrification will inevitably happen when two surfaces contact with each other and triboelectric charges are induced by electron transfer, ion transfer, or material transfer. Contact electrification leads to the formation of a net positive charge on one surface and a net negative charge on the other.…”
Section: Introductionmentioning
confidence: 99%